Kosovo - Public Expenditure Review - World Bank (World Bank, 2012)
During most of the 2000s, Kosovo has pursued a highly conservative fiscal policy, restraining expenditures as revenues continued to climb. The Government has now shifted toward an expansionary expenditure policy. In the short term, the Government intends to finance the resulting budget deficits from accumulated savings and borrowing, as well as through the sale of assets and donor budget support. Neither solution is sustainable. In principle, there is room to increase revenues Kosovo's tax burden is low by regional standards. But the weakness of domestic tax instruments makes this difficult. Restraint on the expenditure side will be required. Given the well-documented shortcomings of public services in Kosovo, this will require an improvement in the quality of public expenditure an improvement in the efficiency of public service delivery rather than a reduction in the quantity or quality of services. This report looks for such opportunities in the major programs of Government expenditure. Overall, Kosovo is in a position to maintain a sustainable fiscal stance while continuing to improve the quality of public services. The public sector is small, relative to gross domestic product (GDP), and does not bear a crushing burden of long term obligations to pensioners, to veterans, to creditors that threaten the finances of neighboring countries.